Al-doped α-MnO2 coated by lignin for high-performance rechargeable aqueous zinc-ion batteries. Issue 56 (1st November 2021) - Xu, Jingliang; Hu, Xinhang; Alam, Md Asraful; Muhammad, Gul; Lv, Yongkun; Wang, Minghai; Zhu, Chenjie; Xiong, Wenlong
Abstract : Al 3+ doping combined with lignin coating improves the structural stability and electrochemical performance of the modified α-MnO2, L + Al@α-MnO2 . Abstract : Zn/MnO2 batteries, one of the most widely studied rechargeable aqueous zinc-ion batteries, suffer from poor cyclability because the structure of MnO2 is labile with cycling. Herein, the structural stability of α-MnO2 is enhanced by simultaneous Al 3+ doping and lignin coating during the formation of α-MnO2 crystals in a hydrothermal process. Al 3+ enters the [MnO6 ] octahedron accompanied by producing oxygen vacancies, and lignin further stabilizes the doped Al 3+ via strong interaction in the prepared material, Al-doped α-MnO2 coated by lignin (L + Al@α-MnO2 ). Meanwhile, the conductivity of L + Al@α-MnO2 improves due to Al 3+ doping, and the surface area of L + Al@α-MnO2 increases because of the production of nanorod structures after Al 3+ doping and lignin coating. Compared with the reference α-MnO2 cathode, the L + Al@α-MnO2 cathode achieves superior performance with durably high reversible capacity (∼180 mA h g −1 at 1.5 A g −1 ) and good cycle stability. In addition, ex situ X-ray diffraction characterization of the cathode at different voltages in the first cycle is employed to study the related mechanism on improving battery performance. This study may provide ideas of designing advanced cathode materials for other aqueous metal-ion batteries.